THE URGENCY OF LIFE SKILLS AND LITERACY SKILLS IN ISLAMIC RELIGIOUS EDUCATION IN THE 21ST CENTURY LEARNING ERA: A LITERATURE REVIEW - Ari Koswara; Rahayu Suprapti; M. Sirozi (LP2M IAI Al-Khairat Pamekasan, 2026)
The rapid development of globalization, digitalization, and technological innovation has significantly transformed the landscape of twenty-first-century education. Education is no longer limited to knowledge transmission but increasingly emphasizes the development of essential competencies required to face complex social and technological challenges. This study aims to analyze the urgency of integrating life skills and literacy skills into Islamic Religious Education (IRE) learning in the twenty-first-century learning context. The research employed a qualitative approach using a library research method that examined various scholarly sources related to Islamic education, twenty-first-century skills, and literacy development. The data sources consisted of scientific journal articles, academic books, research reports, and educational policy documents relevant to the research topic. Data analysis was conducted using content analysis techniques through data reduction, data presentation, and conclusion drawing. The findings indicate that the integration of life skills and literacy skills in Islamic Religious Education plays a significant role in enhancing students’ critical thinking, communication, collaboration, and religious literacy competencies. Furthermore, the integration of these competencies helps students understand Islamic teachings in a more contextual, moderate, and relevant manner in response to contemporary societal changes. Therefore, Islamic Religious Education learning should be developed through innovative approaches such as project-based learning, collaborative learning, and the utilization of digital technology as learning media. The integration of life skills and literacy skills is expected to improve the quality of Islamic education while fostering students who are religiously grounded, critically minded, and adaptable to the challenges of globalization and digital transformation.